Responsible Email Marketing in Higher Education - Vartiak, Lukas; Chrancokova, Martina; Garbarova, Miriam; Fabus, Juraj (International Review of Management and Marketing, 2024)
In higher education, responsible email marketing emerges as a critical strategy for engaging students, alums, and potential students meaningfully and ethically. By comprehensively examining best practices and regulatory compliance, we aim to provide educational institutions with actionable insights for cultivating trust and enhancing communication effectiveness in their email marketing campaigns. This paper explores the nuanced landscape of responsible email marketing within higher education, focusing on balancing effective communication and ethical considerations. The paper aims to identify the starting points for creating a responsible email marketing campaign in higher education. Sources such as Marketing Compare, OmniUpdate, IBM Marketing Cloud and CoSchedule were used for secondary research. The results were formulated based on data published in surveys by RNL, Emma, Oberlo, LeadSquared, Full Fabric, Barnes and Noble, and WordStream. The following scientific research methods were used to create individual parts of the paper: extraction, information collection and processing, comparison, analysis, synthesis and interpretation. By examining current practices, regulatory frameworks, and case studies, we identify strategies institutions can employ to respectfully and effectively engage their audiences. Our analysis highlights the importance of transparency, consent, and personalisation in fostering trust and building long-term relationships with students, alums, and prospective learners.